Comparative analysis of crowd funding in shariah perspective - Saleh, Abdulmajid Obaid Hasan; Ebrahim, Hakim (Universiti Sultan Azlan Shah Malaysia, 2019)
Crowd funding is a new term. However, it has been practiced in Islamic law, for there are some compatible models. Crowd funding is a great tool to test the potentiality of an idea. This paper provides an overview and intensely studies crowd funding in light of Shari’ah in terms of the main types of crowd funding and how to correspond them with Shari’ah.